Mucosal-Associated Invariant T Cells in Regenerative Medicine - Wakao, Hiroshi; Sugimoto, Chie; Kimura, Shinzo; Wakao, Rika (Frontiers in Immunology, 2017)
Although antibiotics to inhibit bacterial growth and small compounds to interfere with the productive life cycle of Human immunodeficiency virus (HIV) have successfully been used to control HIV infection, the recent emergence of the drug-resistant bacteria and viruses poses a serious concern for worldwide public health. Despite intensive scrutiny in developing novel antibiotics and drugs to overcome these problems, there is a dilemma such that once novel antibiotics are launched in markets, sooner or later antibiotic-resistant strains emerge. Thus, it is imperative to develop novel methods to avoid this vicious circle. Here, we discuss the possibility of using induced pluripotent stem cell (iPSC)-derived, innate-like T cells to control infection and potential application of these cells for cancer treatment. Mucosal-associated invariant T (MAIT) cells belong to an emerging family of innate-like T cells that link innate immunity to adaptive immunity. MAIT cells exert effector functions without priming and clonal expansion like innate immune cells, and relay the immune response to adaptive immune cells through production of relevant cytokines. With these characteristics, MAIT cells are implicated in a wide range of human diseases such as autoimmune, infectious, and metabolic diseases, and cancer. Circulating MAIT cells are often depleted by these diseases and often remain depleted even after appropriate remedy because MAIT cells are susceptible to activation-induced cell death and poor at proliferation in vivo, which threatens the integrity of the immune system. Because MAIT cells have a pivotal role in human immunity, supplementation of MAIT cells into immunocompromised patients suffering from severe depletion of these cells may help recapitulate or recover immunocompetence. The generation of MAIT cells from human iPSCs has made it possible to procure MAIT cells lost from disease. Such technology creates new avenues for cell therapy and regenerative medicine for difficult-to-cure infectious diseases and cancer, and contributes to improvement of our welfare.